CONTRADICTIVE AUTOGATE IMPLEMENTATION OF IMMIGRATION STAMP - Nilam Rizky Anugerah; Anindito R. Wiraputra (Polteknik Imigrasi, 2020)
At immigration checkpoints, immigration officials usually place an immigration stamp both on manual and electronic immigration stamps, so that this paper uses a normative juridical approach which is research in this case conducted deductively starting with an analysis of the provisions in the laws and regulations governing problems related to the understanding of entry signs with make the one-door system (autogate) at one of the immigration checkpoints, for that reason it is needed to solve the problem in relation. The sign will not be separated from the stamp. The immigration seal itself translate in the Republic of Indonesia Minister of Law and Human Rights regulation number 28 of 2018 about the Immigration Stamp. Autogate is a means system that greatly helps the process of crossing people, with security on this system itself. However, the understanding of entry signs has deficiencies in explaining or describing the provisions and legal basis on autogate. Every policy in carrying out and even implementing a system.